AL-‘ALĀQAH BAYN AL-NUTQ WA AL-HURŪF FĪ AL-MASĀHIF AL-MABNIYYAH ‘ALĀ AL-RASM AL-‘UŚMĀNĪ: Dirāsah ‘An Al-HKam Warā’a Ikhtilāf Rasm Ba’d Al-Kalimāt Al-Qur’āniyyah ‘Alā Al-Rasm Al-‘Imlā’ī - Sukamta Sukamta (Indonesian Journal of Islamic Literature and Muslim Society, 2018)
The origin of Arabic letters is to write them down as spoken, without adding or subtracting, and without exchanging or changing, thus called standard letters. However, there are a number of words in the Quran that have deviated from this rule written in Ottoman letters. This article discusses the Qur’anic words written by maintaining their authenticity, and the wisdom behind the differences in writing the Quranic words. Using a historical analysis of Qur’anic writing based on seven dialects, it’s concluded that the writing of the Qur’an based on Ottoman letters is intended to maintain the authenticity of the words it uses because it was written as reported by the Prophet. The spelling rules of Ottoman letters lead the Qur’anic words to be read in different ways, which caused in three reasons, namely: there is one word has two readings but is written in one letter; there is one word with two writings that can be written in two letters, and there is one word that has a lot of reading and is written based on this reading. It shows the miracle of Quranic numbers written in Ottoman letters.